Pembentukan dan Pelatihan Dokter Gigi Kecil Di Sekolah Dasar Wilayah Puskesmas Marga II Kabupaten Tabanan Tahun 2018 - Sagung Agung Putri Dwiastuti; I Gusti Ayu Raiyanti; I Gede Surya Kencana; I Made Budi Artawa (Jurnal Pengabmas Masyarakat Sehat, 2019)
Dental health problems in Indonesia are still an unresolved, as can be seen from the 2013 Primary Health Research (Riskesdas) reporting that Indonesia's population suffers from dental caries (tooth decay) 1,4 at the age of 12-14 years, which means at one children suffering from caries 1 to 2 teeth. The results of this study also stated that the prevalence of dental and oral problems in the 12-year age group was 24.8% who received 28.4% treatment, 7% effective medical demand, 95.7% of the community over 12 years old who brushed their teeth every day, only 1.8% brush your teeth properly. According to Astoeti et al. (2006), the optimal dental and oral health status can also be achieved by increasing promotive and preventive efforts as early as the possible ie primary school. The purpose of community service is the formation and training of small dentists to the students in the effort to improve oral hygiene in elementary school in the area of Puskesmas Marga II in 2018, where each elementary school is represented by two people student so that the number of 28 people. The result of community service is as follows: the value of the test before and after the training obtained the average knowledge, better with the criteria is very good. With excellent dental and dental knowledge value, the result of Wilcoxon analysis showed that there was a significant correlation between students' knowledge before and after training with p = 0,000. Student's technique of brushing before the training is got the medium score, after the training is done the very intensive training then got the value with criteria very good,  the result of analysis of Wilcoxon got there is the significant relation of toothbrushing technique of student before and after training with p = 0,000 value.Keywords: knowledge, skills, elementary students